PENERAPAN KOMPONEN MODIFIKASI STRUKTUR RISHA DALAM RANCANGAN ARSITEKTUR RUMAH TINGGAL DENGAN APLIKASI BERBASIS SMARTPHONE - Marisstella Joan; Laurentia Carissa (Riset Arsitektur (RISA), 2023)
Abstract - RISHA (Rumah Instan Sederhana Sehat) is a precast structural technology with a knock-down system, or in other words rebuildable, designed by the Residential Research and Development Center (R&DC) in 2004. RISHA has structural components with limited size of 1.8 m and 3 m. It was eventually developed to expand the size of the P1 component in order to obtain a various ratio for the floor area. The development of RISHA provides a big advantage in residential designs compared to conventional designs. Information technology is one of the media that is very helpful in this modern era. Not a lot of people knows how to use the CAD software, therefore the design of this application will help speed up the process of designing, building, and calculating the costs of RISHA, be it for architects, applicators, as well as potential users. The instant concept will still be fulfilled with this smartphone-based application. The purpose of this research is to continue the research of modified RISHA by designing variations of space modules to accommodate activities residential functions that are adaptive to spaces and number of occupants. In addition, this research aims to design a smartphone application prototype through the Figma website to ease the process of designing and building of RISHA house with its modified components. The method used in this research is qualitative method, namely the design of house plans with modified RISHA based on data from literature studies, and quantitative method from interviews with experienced parties in the RISHA industry to validate the use of smartphone application. As a conclusion of this research, there are three layouts that is able to accommodate human activities in residential houses. Layout A has the structure price of Rp20.976.000,00 up to Rp20.812.000,00 with urban green space as an advantage which also can be an access for daylight sources, however it requires a large site due to the asymmetrical shape of the floor plans. Layout B is the simplest design among the others, the structure costs Rp16.640.000,00 up to Rp18.224.000,00, but the drawback is this layout provides no space for the dining room, therefore it needs to be combined with the family room. Layout C is the widest layout, so it comes with the biggest structure cost which starts from Rp23.888.000,00 up to Rp24.816.000,00. The application will provide the design of residential houses and the structure costs, and users will eventually be directed to the Ministry of Public Works and Housing website to contact the applicator. This application can help applicators, architects, and potential occupants better in the process of designing and building RISHA residential houses. Keywords: Architecture design, RISHA, Information system, Aplication design, Precast concrete